3-D optical and electrical simulation for CMOS image sensors. - Mutoh, H. (IEEE Transactions on electron devices)
The optical and electrical characteristics of CMOS image sensors, such as readout, saturation, reset, charge-voltage conversion, and crosstalk characteristics, are analyzed by a three-dimensional (3-D) device simulator SPECTRA and a 3-D optical simulator TOCCATA which were developed for the analysis of CCD image sensors. The model of readout operation for a buried photodiode with potential barrier and dip is discussed with consideration of thermal diffusion. The transient simulation is executed for readout and reset operation. A novel calculation method for photodiode saturation condition is proposed. The optical and electronic crosstalk is analyzed individually by ray-tracing and current calculation. It is found that the above methods successfully analyze the optical and electrical characteristics of CMOS image sensors.